Preparation process of novel rubber insulating material
By adjusting the proportion and process parameters of composite silicon rubber, unsaturated polyester region molded plastic in the rubber insulation material, form a flame retardant network and insulating barrier, solve the problem of existing rubber insulation material flame retardant and insufficient insulation performance , Achieve higher flame retardant and insulation performance.
Patent Information
- Application Number
- CN202411930329.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The flame retardant and insulation properties of existing rubber insulating materials still need to be further improved, especially in high temperature and high pressure environments.
By mixing composite silicone rubber, unsaturated polyester bulk molding compound, fillers, elastomers, plasticizers, antioxidants and vulcanizing agents, and adjusting the proportions and process parameters of each component, an effective flame retardant network and insulating barrier can be formed , improve the flame retardant and insulation properties of the material.
The flame retardant and insulating properties of rubber insulation materials are significantly improved, and they can maintain good electrical insulation and flame retardant properties in high temperature and high pressure environments to meet more stringent application requirements.
Smart Images

Figure CN119350857A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of insulating materials, in particular to a preparation process of a new rubber insulating material. Background Art
[0002] Rubber materials are a type of polymer material with elasticity and ductility, which are widely used in many fields, such as tires, rubber tubes, seals, etc. Rubber materials have good physical properties and chemical stability, can withstand certain pressure and deformation, and have good insulation properties. These characteristics make rubber materials an ideal choice for the preparation of insulating materials, and are widely used in electrical equipment and the electronics industry. With the advancement of science and technology and the increase in demand, the performance requirements for rubber insulation materials are also getting higher and higher. While they need to have good electrical insulation properties to ensure the safe use of equipment and products, they also need to have good mechanical properties, high and low temperature resistance, and light aging resistance, etc., to adapt to the use requirements under different environments and conditions.
[0003] Chinese patent CN112063061B discloses an insulating material and a preparation method thereof, which uses EPDM rubber, POE elastomer, hydrocarbon resin, silane-modified clay, coupling agent, vulcanizing agent, benzoyl peroxide, activator, softener and antioxidant as raw materials to prepare insulating materials. By using EPDM rubber and POE elastomer together and adding other components, the insulating material obtained has both excellent mechanical properties and aging resistance, and can meet other insulation performance indicators of mining cables, and has excellent electrical insulation performance. However, in the invention, excessively high vulcanization temperature will lead to excessive crosslinking or degradation of rubber molecular chains, thereby reducing the flame retardant properties of the insulating material.
[0004] Chinese patent CN105086325B discloses an EPDM insulation material for cold-resistant cables. The invention uses EPDM and EPDM as base materials, and adds methacrylic acid, hyperbranched acrylate and plasticizer 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, which significantly improves its cold resistance and softness. Plasticizers and hyperbranched acrylates have good compatibility with EPDM and are not prone to migration. Hyperbranched acrylates can make rubber insulation materials have certain elasticity and still have good mechanical properties in cold environments below -50°C. However, excessive amounts of fillers and reinforcing agents in the invention may form conductive channels, resulting in reduced insulation performance.
[0005] In summary, although the new rubber insulation materials prepared by existing technologies have made certain progress, their flame retardant and insulating properties still need to be further improved.
[0006] Therefore, a preparation process of a new rubber insulation material is proposed. Summary of the invention
[0007] The purpose of the present invention is to provide a preparation process of a new rubber insulation material, and the new rubber insulation material is obtained by mixing composite silicone rubber, unsaturated polyester bulk molding compound, filler, elastomer, plasticizer, antioxidant and vulcanizer. By preparing composite silicone rubber, changing the mass ratio of aluminum hydroxide particles, nano-montmorillonite and short glass fiber, the diameter of short glass fiber, the mass ratio of mixture one and curing agent, rotation speed and curing time; preparing elastomer, changing the amount of catalyst, polymer temperature, polymer stirring time and the amount of elastomer, an effective flame retardant network can be formed to improve the flame retardant performance of rubber materials; by changing the phenyl content in phenyl silicone rubber, the average molecular weight, viscosity and DMC amount of phenyl silicone rubber; preparing modified barium titanate, changing the reflux reaction temperature, drying temperature and the amount of modified barium titanate; changing the mixing temperature and time of mixture one, changing the temperature and time of two vulcanizations, the insulation performance of rubber materials is improved.
[0008] To achieve the above object, the present invention provides the following technical solutions: It should be noted that all parts in the present invention are parts by mass.
[0009] A preparation process of a new rubber insulation material, the preparation process of the new rubber insulation material is as follows: Aluminum hydroxide particles, nano-montmorillonite and short glass fibers are sequentially added to the rubber base material in a mass ratio of 5-10:1.2:1, and mixed and stirred for 10 minutes to obtain a mixture one; the mixture one and the curing agent methyltrimethoxysilane are evenly mixed in a mass ratio of 8-12:1.5, and stirred at a speed of 150-250r / min for 5 minutes to obtain a mixture two; the mixture two is degassed using a vacuum pump, and then placed in an oven and cured at 150°C for 18-28 minutes to obtain a composite silicone rubber; 1,2,4-trichlorobenzene, hexachlorocyclotriphosphazene, a catalyst and an accelerator are mixed uniformly, and stirred at 150-200° C. for 3.5-4.5 hours to obtain a polymer; petroleum ether is added to the polymer, and the mixture is allowed to stand, filtered and dried to obtain an elastomer; Add the composite silicone rubber into a kneader and stir it, then add unsaturated polyester bulk molding compound, filler and elastomer, and mix at 100°C-120°C for 15min-25min to obtain mixture one; add plasticizer and antioxidant into mixture one, and continue mixing for 8min to obtain mixture two; calender and extrude mixture two to obtain a rubber compound; add a vulcanizing agent into the rubber compound and vulcanize it to obtain a new rubber insulation material.
[0010] Preferably, in parts by mass, the amount of composite silicone rubber is 80 parts; the amount of elastomer is 5-15 parts; the amount of plasticizer is 1.2 parts; the amount of vulcanizer is 0.8 parts; the amount of antioxidant is 2 parts; the amount of filler is 0.8-1.8 parts; and the amount of unsaturated polyester bulk molding compound is 30-40 parts.
[0011] Preferably, the plasticizer is cyclohexane oil; the vulcanizer is diisopropylbenzene peroxide; the antioxidant is 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline; and the filler is modified barium titanate.
[0012] Preferably, the diameter of the short glass fibers is 8-12 μm.
[0013] Preferably, the rubber base material is phenyl silicone rubber; the mass content percentage of phenyl in the phenyl silicone rubber is 10-20wt%; the average molecular weight of the phenyl silicone rubber is 500000-700000; and the viscosity of the phenyl silicone rubber is 20-30×106 mPa·s.
[0014] Preferably, the preparation process of modified barium titanate is as follows: adding nano barium titanate powder to a hydrogen peroxide solution, reflux reacting at 110-120°C for 3.5 hours, filtering to obtain a solid powder; washing the solid powder three times with deionized water and acetone solution respectively to obtain pretreated barium titanate; drying the pretreated barium titanate in an oven at 90-100°C for 20 hours to obtain modified barium titanate.
[0015] Preferably, the elastomer preparation process is as follows: add 35 parts of 1,2,4-trichlorobenzene into a three-necked flask, add 10 parts of hexachlorocyclotriphosphazene, 0.5-1.0 parts of catalyst carbamic acid and 1.2 parts of accelerator gypsum thereto while stirring, raise the temperature to 175°C and stir for 4.0 hours to obtain a polymer; add petroleum ether to the polymer, let it stand, filter to obtain a precipitate; put the precipitate into a vacuum oven to dry to remove residual solvent, and obtain an elastomer.
[0016] Preferably, high temperature vulcanization is divided into primary vulcanization and secondary vulcanization.
[0017] Preferably, the first vulcanization reaction temperature is 140-160° C., and the reaction time is 35-45 min; the second vulcanization reaction temperature is 210-240° C., and the reaction time is 40-60 min.
[0018] Preferably, the calendering extrusion temperature is; the vacuum degree is 1.3 MPa.
[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. Aluminum hydroxide particles will decompose and absorb a large amount of heat at high temperatures, while producing water vapor, which helps to dilute combustible gases and reduce temperatures; nano-montmorillonite can form a carbon layer at high temperatures, preventing the transfer of heat and oxygen and delaying the combustion process; short glass fibers are not easy to burn at high temperatures and can form a stable carbon layer, which helps to prevent the spread of flames. The present invention can play a synergistic role and increase the flame retardant properties of the material by mixing the three in a certain mass ratio. By changing the diameter of the short glass fibers, the material can reduce cracks and gaps generated during the combustion process, thereby preventing the further spread of the flame to a certain extent; by changing the mass ratio of the mixture and the curing agent, the rotation speed and the curing time, the density of the cross-linked network can be increased, so that the transfer of heat and oxygen is hindered, thereby delaying the combustion process and improving the flame retardant properties of the composite silicone rubber.
[0020] 2. The elastomer prepared using hexachlorocyclotriphosphazene can form a complete rigid ablation layer during the ablation process, and the burnt layer is composed of many upright "coral fleece-like" hollow graphite microtubes, which can be used as a heat-resistant layer for further ablation, thereby improving the ablation performance of the material. The present invention can form an effective flame retardant layer or flame retardant network and improve the flame retardant performance of the rubber material by changing the amount of catalyst, polymer temperature, polymer stirring time and the amount of elastomer in the preparation process of the elastomer.
[0021] 3. Phenyl has a large steric effect and strong molecular chain rigidity. As the phenyl content in phenyl silicone rubber increases, the dipole moment of the polar group decreases, and the conjugated benzene ring has a large electron affinity, which can capture high-energy electrons and dissipate energy, and can significantly improve the insulation performance of the material. The present invention can form a more stable and compact structure after curing by changing the phenyl content in phenyl silicone rubber and the average molecular weight and viscosity of phenyl silicone rubber, and is less prone to electrical breakdown or leakage; by changing the amount of unsaturated polyester bulk molding compound (DMC), it can synergistically increase the insulation performance of the material with silicone rubber.
[0022] 4. The present invention modifies the surface of barium titanate and adds active hydroxyl groups on the surface of barium titanate particles, so that it can be dispersed more evenly in the rubber matrix, reduce local electric field concentration, and thus improve insulation performance. By changing the reflux reaction temperature and drying temperature during the preparation process, its dispersibility and interface interaction can be improved to avoid crystal defects; by changing the amount of modified barium titanate, an effective insulation barrier can be formed to improve the insulation performance of the material.
[0023] 5. The present invention can fully mix various raw materials and form a homogeneous rubber insulating material by changing the mixing temperature and time of the mixture, so that the electrical properties inside the material are relatively uniform; by performing secondary vulcanization on the rubber material and changing the temperature and time of the two vulcanizations, it is helpful to further promote the cross-linking reaction of the rubber, consolidate the cross-linking network, and eliminate the residual stress generated during the first vulcanization process, thereby improving the insulation performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a graph showing the insulation performance test results of Examples 35, 39-46 of the present invention and Comparative Examples 3-4. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] See also Figure 1 The present invention provides a preparation process of a new rubber insulation material, and the technical solution is as follows: The substance information involved in the present invention is as follows: Methyltrimethoxysilane CAS: 1185-55-3; 1,2,4-trichlorobenzene CAS: 120-82-1; Hexachlorocyclotriphosphazene CAS: 940-71-6; Petroleum ether CAS: 8032-32-4; Diisopropylbenzene peroxide CAS: 80-43-3; 6-ethoxy-2,2,4,-trimethyl-1,2-dihydroquinoline CAS: 91-53-2; Nano-barium titanate CAS: 12047-27-7; Hydrogen peroxide CAS: 7722-84-1; Propylene Ketone CAS: 67-64-1; aminoacetic acid CAS: 463-77-4; aluminum hydroxide particles were purchased from Wuhan Jiyesheng Chemical Co., Ltd.; nano-montmorillonite was purchased from Zhejiang Fenghong New Materials Co., Ltd.; short glass fiber was purchased from Changchun Man-Made Resin Factory Co., Ltd.; unsaturated polyester bulk molding compound (DMC) was purchased from Yuanfa New Materials Co., Ltd.; cyclohexane oil was purchased from Jiangsu Bost Chemical Technology Co., Ltd.; phenyl silicone rubber was purchased from Chengdu Senfa Rubber and Plastic Co., Ltd.; and plaster of Paris was purchased from Beijing Chemical Plant Co., Ltd.
[0027] Example 1 Aluminum hydroxide particles, nano-montmorillonite and short glass fibers were added to the rubber base material in a mass ratio of 5:1.2:1, and the mixture was stirred for 10 minutes to obtain a mixture 1; the mixture 1 and the curing agent methyltrimethoxysilane were mixed evenly in a mass ratio of 8:1.5, and stirred at a speed of 150r / min for 5 minutes to obtain a mixture 2; the mixture 2 was degassed using a vacuum pump, and then placed in an oven and cured at 150°C for 18 minutes to obtain a composite silicone rubber; the diameter of the short glass fiber was 8μm; the rubber base material was phenyl silicone rubber; the mass content percentage of phenyl in the phenyl silicone rubber was 10wt%; the average molecular weight of the phenyl silicone rubber was 500000; the viscosity of the phenyl silicone rubber was 20×10 6 mPa·s; Add 3 parts of nano-barium titanate powder to 50 parts of hydrogen peroxide solution, reflux for reaction at 110° C. for 3.5 hours, and filter to obtain solid powder; wash the solid powder three times with deionized water and acetone solution respectively to obtain pretreated barium titanate; dry the pretreated barium titanate in an oven at 90° C. for 20 hours to obtain modified barium titanate; 35 parts of 1,2,4-trichlorobenzene were added into a three-necked flask, and 10 parts of hexachlorocyclotriphosphazene, 0.5 parts of carbamic acid as a catalyst and 1.2 parts of plaster of Paris as an accelerator were added thereto while stirring, and the temperature was raised to 150° C. and stirred for 3.5 hours to obtain a polymer; 50 parts of petroleum ether were added to the polymer, and the mixture was allowed to stand and filtered to obtain a precipitate; the precipitate was placed in a vacuum oven and dried to remove the residual solvent to obtain an elastomer; 80 parts of composite silicone rubber are added into a kneader for stirring, followed by adding 30 parts of unsaturated polyester bulk molding compound, 0.8 parts of filler-modified barium titanate and 5 parts of elastomer, and kneading at 100°C for 15 minutes to obtain mixture one; 1.2 parts of plasticizer cyclohexane oil and 2 parts of antioxidant 6-ethoxy-2,2,4,-trimethyl-1,2-dihydroquinoline are added into mixture one, and kneading is continued for 8 minutes to obtain mixture two; mixture two is calendered and extruded to obtain a rubber compound; 0.8 parts of vulcanizing agent diisopropylbenzene peroxide is added into the rubber compound for vulcanization to obtain a new rubber insulation material; vulcanization is divided into primary vulcanization and secondary vulcanization; the primary vulcanization reaction temperature is 140-160°C, and the reaction time is 35-45 minutes; the secondary vulcanization reaction temperature is 210-240°C, and the reaction time is 40-60 minutes; the calendering extrusion temperature is 95°C; and the vacuum degree is 1.3MPa.
[0028] Embodiment 2-14 Referring to the preparation method and parameter conditions of Example 1, the specific differences are shown in Table 1.
[0029] Table 1 Specific preparation parameters of Examples 2-14
[0030] Example 15 Flame retardant performance test The vertical burning grade was measured using a vertical burning instrument in accordance with the UL94-2018 standard. The sample size was 125 mm × 13 mm × 3 mm. The vertical burning grade classification is shown in Table 2.
[0031] Table 2 Vertical combustion level classification
[0032] The test was carried out in accordance with the national standard "GB / T6553-2003 Test method for evaluating the resistance of electrical insulating materials to tracking and corrosion used in harsh environmental conditions". A voltage of 4.5 kV was applied to both ends of the sample while dripping dirty liquid, and the time required for the sample to burn through was tested; the results are shown in Table 3.
[0033] Table 3 Flame retardant performance test of Examples 1-14
[0034] Aluminum hydroxide particles are a commonly used inorganic flame retardant. They decompose and absorb a large amount of heat at high temperatures, while producing water vapor, which helps dilute combustible gases and reduce temperatures. Nano-montmorillonite can form a carbon layer at high temperatures, preventing the transfer of heat and oxygen, thereby delaying the combustion process. Glass fiber is not easy to burn at high temperatures, and can form a stable carbon layer, which helps prevent the spread of flames. The three are mixed in a certain proportion to play a synergistic role and increase the flame retardant properties of the material. As can be seen from Table 3, in Examples 1-3, when the content of aluminum hydroxide particles increases, its decomposition reaction can consume more heat and produce more water vapor to dilute combustible gases, thereby improving the flame retardant properties of the composite silicone rubber; however, too high a content of aluminum hydroxide particles may cause the mechanical properties of the composite silicone rubber to decrease, thereby reducing its overall performance. In Examples 2, 4-5, as the mass ratio of mixture 1 to curing agent increases, the density of the cross-linked network increases, so that the transfer of heat and oxygen is hindered, thereby delaying the combustion process and improving the flame retardant properties of the composite silicone rubber; however, when the mass ratio of the two is too high, the excessively high cross-linking density causes the material to become brittle and hard, and is prone to breakage and falling off during the combustion process, thereby reducing the flame retardant effect. In Examples 4, 6-7, the smaller the diameter of the short glass fiber, the greater its surface area to volume ratio, and the tighter the structure. In a high temperature environment, short glass fibers with small diameters can better withstand high temperatures and reduce the possibility of thermal decomposition, thereby maintaining the structural stability of the material, and can reduce cracks and voids generated during the combustion process, thereby preventing the further spread of the flame to a certain extent; however, short glass fibers with too small a diameter are more likely to break when subjected to stress, thereby reducing the flame retardant properties of the material. In Examples 6, 8-11, too slow a stirring speed will cause the dispersed components to re-agglomerate, forming larger particles or lumps, forming stress concentration points, and affecting the flame retardant properties of the material; when the stirring speed is too fast, the rubber molecular chain will be subjected to excessive shearing, resulting in molecular chain breakage or damage to the cross-linked network, and too fast a stirring speed will introduce bubbles, which may form defects during the curing process, affecting the density of the material, thereby reducing the flame retardant properties of the composite silicone rubber. In Examples 10, 12-14, when the curing time is too short, the curing agent and the rubber base material cannot fully react, resulting in incomplete formation of the cross-linked network, which will affect the overall structural strength of the composite silicone rubber and further affect its flame retardant properties; when the curing time is too long, the curing agent and the rubber base material react excessively, resulting in an overly dense cross-linked network, making the composite silicone rubber too hard and brittle, affecting its flame retardant properties.In Example 12, when the mass ratio of aluminum hydroxide particles, nano-montmorillonite and short glass fibers is 8:1.2:1, the mass ratio of mixture 1 and curing agent is 10:1.5, the diameter of the short glass fibers is 10 μm, the stirring speed is 220 r / min and the curing time is 22 min, the prepared composite silicone rubber can be used in new rubber insulation materials to achieve the best flame retardant properties, the vertical burning grade can reach V0 level, and the leakage current tracking time at 4.5 kV reaches 282 min.
[0035] Examples 16-25 Referring to the preparation method and parameter conditions of Example 12, the specific differences are shown in Table 4.
[0036] Table 4 Specific preparation parameters of Examples 16-25
[0037] Comparative Example 1 A new rubber insulating material was prepared according to the method of Example 12, except that no elastomer was added.
[0038] Example 26 Flame retardant performance test The vertical burning grade is measured using a vertical burning instrument according to the UL94-2018 standard, and the sample size is 125mm×13mm×3mm; the vertical burning grade classification is shown in Table 2; The test was carried out in accordance with the national standard "GB / T6553-2003 Test method for evaluating the resistance of electrical insulating materials to tracking and corrosion used in harsh environmental conditions". A voltage of 4.5 kV was applied to both ends of the sample while dirty liquid was dripped, and the time required for the sample to burn through was tested. The results are shown in Table 5.
[0039] Table 5 Flame retardant performance test of Examples 12, 16-25 and Comparative Example 1
[0040] The elastomer prepared using hexachlorocyclotriphosphazene can form a complete rigid ablation layer during the ablation process, and the burnt layer is composed of many upright "coral fleece-like" hollow graphite microtubes, which can be used as a heat-resistant layer for further ablation, thereby improving the ablation performance of the material. As can be seen from Table 5, in Examples 12, 16-17, when the amount of catalyst is too small, the polymerization reaction is incomplete, resulting in a decrease in the conversion rate of the reactants, thereby affecting the flame retardant properties of the elastomer; when the amount of catalyst is too large, it will affect the chain structure and cross-linking density of the polymer, increase the heterogeneity of the polymer network, and thus reduce the flame retardant properties. In Examples 16, 18-19, too low a polymer temperature will lead to insufficient cross-linking points in the polymer network, weakening the interaction between polymer chains, thereby reducing the flame retardant properties; when the polymer temperature is too high, it will cause the polymer chain to break or cross-link excessively, and high temperature will also cause the polymer to undergo oxidative degradation, thereby reducing the flame retardant properties of the material. In Examples 18, 20-21, when the polymer stirring time is too short, the crosslinking points in the polymer network are insufficient, so that the interaction between the polymer chains is weakened, thereby reducing the flame retardant performance; when the stirring time is too long, the polymer chain will be over-sheared, and the polymer will be exposed to high temperature for a long time, which will increase the risk of polymer degradation and affect the flame retardant performance of the elastomer. In Examples 20, 22-25, the amount of elastomer is too small to form an effective flame retardant layer or flame retardant network, resulting in insufficient flame retardant performance of the rubber material; with the increase of the amount of elastomer, the flame retardant performance of the rubber material will be further improved, but when the amount reaches a certain level, the improvement of the flame retardant performance of the rubber material will tend to be flat or even no longer improve. In Example 24, when the catalyst dosage is 0.7 parts, the polymer temperature is 175 ° C, and the polymer stirring time is 4.0h, the elastomer is prepared, and when 12 parts of the elastomer are added to the rubber material, the flame retardant performance of the obtained rubber insulation new material is the best, the vertical burning grade is V0, and the tracking time at 4.5kV is 305min. In Comparative Example 1, no elastomer was added to the new rubber insulating material, so its flame retardant performance was greatly reduced, the vertical burning level did not reach V2, and the leakage current tracking time at 4.5 kV was only 218 minutes.
[0041] Examples 27-37 Referring to the preparation method and parameter conditions of Example 24, the specific differences are shown in Table 6.
[0042] Table 6 Specific preparation parameters of Examples 27-37
[0043] Comparative Example 2 A new rubber insulation material was prepared according to the method of Example 24, except that no DMC was added.
[0044] Example 38 Insulation Performance Test The volume resistivity is tested according to GB / T1410-2006 standard; The insulation strength was tested according to GB / T1408.1-2006 standard; the results are shown in Table 7.
[0045] Table 7 Insulation performance test of Examples 24, 27-37
[0046] As can be seen from Table 7, in Examples 24, 27-29, the phenyl group has a large steric effect, and the molecular chain is rigid. As the phenyl content in the phenyl silicone rubber increases, the dipole moment of the polar group decreases, and the conjugated benzene ring has a large electron affinity, which can capture high-energy electrons and dissipate energy, and can significantly improve the insulation performance of the material; however, too much phenyl content will destroy the symmetry and integrity of the silicone rubber, limit the stretching of the molecular chain, and cause the mechanical properties to be greatly reduced, thereby affecting its insulation performance. In Examples 28, 30-32, the average molecular weight of the phenyl silicone rubber is changed. The low molecular weight phenyl silicone rubber has insufficient strength and elasticity, and cannot withstand the stress and strain during use, which will cause the insulation layer to rupture or damage, and due to its insufficient strength and elasticity, electrical breakdown or leakage is prone to occur; as the molecular weight of the phenyl silicone rubber increases, the strength and elasticity are also improved, which helps to maintain its structural stability, thereby improving the insulation performance, but too high a molecular weight will make it difficult to process and shape, and the rubber may become too hard, causing it to crack or be damaged during use, thereby affecting the insulation performance. In Examples 31, 33-34, as the viscosity of the phenyl silicone rubber increases, it can form a more stable and compact structure after curing, which can effectively prevent current leakage and improve the electrical insulation performance of the material; however, phenyl silicone rubber with too high a viscosity will cause internal stress concentration due to processing difficulties, increase the risk of cracks during aging, and thus reduce the insulation performance. In Examples 33, 35-37, DMC has better electrical insulation performance than the rubber matrix. Changing the amount of DMC, when the amount of DMC is too small, it is not enough to improve the insulation effect, and excessive DMC will cause uneven dispersion, or even aggregation, resulting in defects in the matrix and reduced electrical insulation performance of the composite material. In Example 35, when the phenyl content in the phenyl silicone rubber is 16wt%, the average molecular weight of the phenyl silicone rubber is 600000, and the viscosity of the phenyl silicone rubber / mPa·s is 25×10 6 When the amount of DMC is 34 parts, the insulation performance of the rubber insulation material is the best, with a dielectric strength of 31.6 kV / mm and a volume resistivity of 7.2×10 15 Ω·m. In comparative example 2, the insulation performance of the new rubber insulation material prepared without adding DMC was greatly reduced, the insulation strength was only 19.4kV / mm, and the volume resistivity was reduced to 5.5×10 13 Ω·m.
[0047] Examples 39-46 Referring to the preparation method and parameter conditions of Example 35, the specific differences are shown in Table 8; the drying temperature in Table 8 is the drying temperature of the pretreated barium titanate.
[0048] Comparative Example 3 A new rubber insulation material was prepared according to the method of Example 35, except that the barium titanate was not modified.
[0049] Comparative Example 4 A new rubber insulating material was prepared according to the method of Example 35, except that no filler was added.
[0050] Example 47 Insulation Performance Test The volume resistivity is tested according to GB / T1410-2006 standard; The insulation strength was tested according to GB / T1408.1-2006 standard; the results are as follows Figure 1 and as shown in Table 8.
[0051] Table 8 Insulation performance test of Examples 35, 39-46, and Comparative Examples 3-4
[0052] Surface modification of barium titanate and adding active hydroxyl groups to the surface of barium titanate particles can make it more evenly dispersed in the rubber matrix, reduce local electric field concentration, and thus improve insulation performance. Figure 1It can be seen from Table 8 that in Examples 35, 39-41, the reflux temperature affects the crystal structure of barium titanate, including grain size and crystal defects, and a moderate reflux temperature helps to improve its dispersibility and interface interaction, thereby improving the insulation performance. A reflux temperature that is too low will not only lead to incomplete reaction, but also produce more crystal defects; a reflux temperature that is too high will lead to larger barium titanate grains, poor dispersibility, and increased local electric field concentration, thereby reducing the insulation performance. The drying temperature will affect the surface hydroxyl content and surface energy of the barium titanate powder. In Examples 40, 42-43, when the drying temperature is too low, the water in the barium titanate powder will not be completely removed, affecting the dispersibility of the powder and its compatibility with the rubber matrix, thereby reducing the insulation performance; when the drying temperature is too high, the barium titanate powder will cause lattice distortion or grain growth, which will also reduce its dispersibility in the rubber and its compatibility with the rubber matrix. In Examples 42, 44-46, when the amount of filler is too small, an effective insulation barrier cannot be formed, and the improvement of the insulation performance of the material is limited; when the amount of filler is too large, its distribution in the rubber insulation material becomes dense, resulting in a too high dielectric constant of the material, which may increase the capacitance effect of the material, resulting in uneven electric field distribution, increasing the risk of insulation breakdown, and reducing insulation strength. In Example 45, when the reflux temperature is 114°C and the modified barium titanate is obtained by drying at 95°C, and 1.5 parts of modified barium titanate are used as fillers, the insulation strength of the obtained rubber insulation new material is 34.0 kV / mm, and the volume resistivity is 1.3×10 15 Ω·m, and its insulation performance is the best. In comparative example 3, unmodified barium titanate is used as filler, and its dispersion in the polymer matrix is poor, resulting in reduced insulation performance of the new rubber insulation material, with a dielectric strength of 24.3 kV / mm and a volume resistivity of 8.9×10 13 Ω·m. In Comparative Example 4, no filler was added to the new rubber insulation material, and its insulation strength was 19.7 kV / mm and its volume resistivity was 6.2×10 13 Ω·m, the insulation performance is significantly reduced.
[0053] Examples 48-58 Referring to the preparation method and parameter conditions of Example 45, the specific differences are shown in Table 9.
[0054] Table 9 Specific preparation parameters of Examples 48-58
[0055] Comparative Example 5 A new rubber insulating material was prepared according to the method of Example 45, except that vulcanization was performed only once.
[0056] Example 61 Insulation Performance Test The volume resistivity is tested according to GB / T1410-2006 standard; The insulation strength was tested according to GB / T1408.1-2006 standard; the results are shown in Table 10.
[0057] Table 10 Insulation performance test of Examples 45, 48-60 and Comparative Example 5
[0058] As can be seen from Table 10, in Examples 45, 48-50, if the mixing temperature is too low, the fluidity of the raw materials will deteriorate, resulting in uneven mixing; if the mixing temperature is too high, the rubber molecular chain will be degraded and the cross-linking reaction will occur prematurely. The degradation of the molecular chain will reduce the insulation performance of the rubber, and the premature cross-linking reaction will cause the material to be unable to fully cross-link in the subsequent vulcanization process, which will also affect the insulation performance. In Examples 49, 51-52, the mixing time is changed. The appropriate mixing time can make the various raw materials fully mixed and uniform to form a homogeneous rubber insulating material. When the mixing time is too short, the components cannot be fully mixed and uniform, resulting in an uneven structure inside the rubber insulating material, so that the electrical properties of different regions are different, thereby affecting the insulation performance of the material; if the mixing time is too long, the rubber molecular chain will break and degrade, increasing the risk of current leakage, thereby reducing the insulation performance of the rubber insulating material. In Examples 51, 53-60, the temperature of the first vulcanization is limited, so that the rubber material can be fully cross-linked and will not be degraded due to excessively high temperature. The formation of a cross-linked network can limit the movement of the molecular chain, thereby reducing current leakage. Increasing the temperature for secondary vulcanization can help further promote the cross-linking reaction of the rubber, consolidate the cross-linking network, and eliminate the residual stress generated during the first vulcanization process. Changing the time of the two vulcanizations can allow the cross-linking reaction to proceed gradually until it reaches a relatively stable state, avoiding excessive cross-linking of the rubber due to too long a time, resulting in hardening and brittleness, which affects the insulation performance. In Example 59, the mixture was kneaded at 115°C for 20 minutes, the first vulcanization temperature of the rubber was 150°C, the time was 38 minutes, and the secondary vulcanization temperature was 225°C, the time was 50 minutes, the insulation performance of the obtained new rubber insulation material was the best, the insulation strength reached 39.5kV / mm, and the volume resistivity reached 7.2×10 15 Ω·m. In Comparative Example 5, the rubber material is vulcanized only once, which will form low molecular weight compounds that affect the mechanical properties of the silicone rubber, and the crosslinking density of the silicone rubber is insufficient, which ultimately leads to reduced insulation performance. The insulation strength of the obtained rubber insulation material is 28.7 kV / mm, and the volume resistivity is 8.7×10 14 Ω·m.
[0059] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A preparation process of a new rubber insulation material, characterized in that: the preparation process of the new rubber insulation material is as follows: Aluminum hydroxide particles, nano-montmorillonite and short glass fibers are mixed at a ratio of 5-10: The mixture is added into the rubber base material in a mass ratio of 1.2:1 in sequence, and mixed and stirred for 10 minutes to obtain a mixture one; the mixture one and the curing agent methyltrimethoxysilane are mixed evenly in a mass ratio of 8-12:1.5, and stirred at a speed of 150-250r / min for 5 minutes to obtain a mixture two; the mixture two is degassed using a vacuum pump, and then placed in an oven and cured at 150°C for 18-28 minutes to obtain a composite silicone rubber; 1,2,4-trichlorobenzene, hexachlorocyclotriphosphazene, a catalyst and an accelerator are mixed uniformly, and stirred at 150-200° C. for 3.5-4.5 hours to obtain a polymer; petroleum ether is added to the polymer, and the mixture is allowed to stand, filtered and dried to obtain an elastomer; The composite silicone rubber is added into a kneader for stirring, and then unsaturated polyester bulk molding compound, filler and the elastomer are added, and kneading is carried out at 100° C.-120° C. for 15 min-25 min to obtain a mixture one; a plasticizer and an antioxidant are added into the mixture one, and the kneading is continued for 8 min to obtain a mixture two; the mixture two is calendered and extruded to obtain a rubber compound; a vulcanizing agent is added into the rubber compound for vulcanization to obtain the new rubber insulation material.
2. The preparation process of a new rubber insulation material according to claim 1 is characterized in that: In parts by mass, the amount of the composite silicone rubber is 80 parts; the amount of the elastomer is 5-15 parts; the amount of the plasticizer is 1.2 parts; the amount of the vulcanizer is 0.8 parts; the amount of the antioxidant is 2 parts; the amount of the filler is 0.8-1.8 parts; and the amount of the unsaturated polyester bulk molding compound is 30-40 parts.
3. The preparation process of a new rubber insulation material according to claim 2 is characterized in that: The plasticizer is cyclohexane oil; the vulcanizer is diisopropylbenzene peroxide; the antioxidant is 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline; and the filler is modified barium titanate.
4. The preparation process of a new rubber insulation material according to claim 1 is characterized in that: The diameter of the short glass fibers is 8-12 μm.
5. The preparation process of a new rubber insulation material according to claim 1 is characterized in that: The rubber base material is phenyl silicone rubber; the mass content percentage of phenyl in the phenyl silicone rubber is 10-20wt%; the average molecular weight of the phenyl silicone rubber is 500000-700000; the viscosity of the phenyl silicone rubber is 20-30×10 6 mPa·s.
6. The preparation process of a new rubber insulation material according to claim 3 is characterized in that: The preparation process of the modified barium titanate is as follows: adding nano barium titanate powder to a hydrogen peroxide solution, reflux reacting at 110-120° C. for 3.5 hours, filtering to obtain a solid powder; washing the solid powder three times with deionized water and acetone solution respectively to obtain pretreated barium titanate; drying the pretreated barium titanate in an oven at 90-100° C. for 20 hours to obtain the modified barium titanate.
7. The preparation process of a new rubber insulation material according to claim 1 is characterized in that: The elastomer preparation process is as follows: 35 parts of the 1,2,4-trichlorobenzene are added into a three-necked flask, 10 parts of the hexachlorocyclotriphosphazene, 0.5-1.0 parts of the catalyst carbamic acid and 1.2 parts of the accelerator plaster are added thereto while stirring, the temperature is raised to 175° C. and stirred for 4.0 hours to obtain the polymer; petroleum ether is added into the polymer, the mixture is allowed to stand, and a precipitate is obtained by filtering; the precipitate is placed in a vacuum oven and dried to remove the residual solvent to obtain the elastomer.
8. The preparation process of a new rubber insulation material according to claim 1 is characterized in that: The vulcanization is divided into primary vulcanization and secondary vulcanization.
9. The preparation process of a new rubber insulating material according to claim 8, characterized in that: The temperature of the first vulcanization reaction is 140-160° C., and the reaction time is 35-45 minutes; the temperature of the second vulcanization reaction is 210-240° C., and the reaction time is 40-60 minutes.
10. The preparation process of a new rubber insulation material according to claim 1, characterized in that: The calendering extrusion temperature is 95° C. and the vacuum degree is 1.3 MPa.
Citation Information
Patent Citations
An ethylene propylene rubber insulation material for cold-resistant cables
CN105086325B
An insulating material and its preparation method
CN112063061B
Phenyl siloxane rubber nanometer composite material and preparation method thereof
CN104031388A
Chemical-corrosion-resistant insulating material and preparation method thereof
CN112920488A